Analisis Faktor-Faktor Penunjang dan Penghambat Kinerja Birokrasi Sekretariat daerah Kabupaten Kepulauan Talaud - Laloma, Alden (JURNAL ILMU ADMINISTRASI (JIA), 2013)
Abstracts: This study moved from the indication of poor performance on the bureaucratic apparatus of the Regional Secretariat Talaud Islands. This condition is thought to be related to cultural factors and paternalistic leadership as a factor in the performance improvement pengambat. Thus, this study seeks to answer these problems in addition to simultaneously aims to assess and understand the performance of the bureaucratic apparatus adapted to the duties and functions in line with the achievement of the vision, mission and goals of the organization as well as to identify and analyze whether the leadership and culture are factors supporting or inhibiting the achievement of performance bureaucracy at the Regional Secretariat Talaud Islands. The results of the data analysis showed that the application of leadership and organizational culture at the Regional Secretariat Talaud Islands cendering paternalistic still characterized by a significant degree of dependence of the subordinates (employees) to the supervisor (leader), however, the pattern of visionary and transformative leadership and organizational culture modern began to appear in the process of implementation of the tasks and functions of the organization. Keywords: Leadership, Culture, Performance, Bureaucratic, Apparatus